Single-center experience with percutaneous mitral valve repair using the MitraClip in a high-risk series in Turkey - Cüneyt Toprak; Gökhan Kahveci; Alev Kılıcgedik; Cevat Kırma; Selcuk Pala; Mustafa Bulut; Cihangir Kaymaz; Nihal Ozdemir; İbrahim Akın İzgi; Mehmet Inanır; Anıl Avcı; Ali Metin Esen (KARE Publishing, 2016)
Objective: Mitral valve regurgitation (MR) is the second most common heart valve disease in Europe. Without intervention, prognosis of severe symptomatic MR is poor. Percutaneous edge-to-edge mitral valve repair with MitraClip is a promising mitral regurgitation treatment technique in select, high-surgical-risk patients. The present objective was to describe the experience of a single center with MitraClip use in a high-risk series in Turkey. Methods: Between May 2013 and September 2014, 28 high-surgical-risk patients with MR of at least grade 3+ and mean EuroSCORE of 26% underwent MitraClip implantation at our institution. In-hospital and follow-up safety and efficacy results are presented. Results: Mean patient age was 58 years, and 75% were male. Grade 3 or 4 MR was present in all patients, and was primarily the result of restrictive functional mitral regurgitation (in 89% of cases). Mean left ventricular ejection fraction (LVEF) was 27% and New York Heart Association (NYHA) classification was III or IV in 89% of the population. Acute procedural success was 89%, with 47% of patients receiving a single clip, 39% receiving 2 clips, and 14% receiving 3 clips. One periprocedural death occurred, and 2 deaths occurred during follow-up (mean: 13.9 months). After 1 year, more than 75% of patients had MR severity of ≤2+ and NYHA classification of I or II, but no significant change in left ventricular volume or systolic function. Significant improvement in 6-minute walk test and quality of life was also observed. Conclusion: Initial experience with the MitraClip system showed promising results in patients considered high-surgical-risk, particularly in those with end-stage heart failure.